Association between perception of COVID-19 risk, confidence in health services and avoidance of emergency department visits: results from a community-based survey in Portugal - Silvia Lopes; Sónia Dias; Ana Gama; Pedro Laires; Carla Nunes; Patrícia Soares; Ana Rita Pedro; Marta Moniz; Ana Rita Goes (BMJ Open)
Objectives To examine the association between the perception of COVID-19 risk, confidence in health services and avoidance of emergency department (ED) visits in Portugal during the COVID-19 pandemic.Design Community-based, cross-sectional survey.Setting Volunteer sample that completed the online survey between April 2020 and May 2021.Participants 987 participants who perceived needing ED care. Of those, 242 reported avoiding ED visits.Outcome measures Logistic regression models for ED avoidance were conducted to estimate the effect of risk perception and confidence in health services, adjusted for sociodemographics, health status and time.Results The adjusted odds for ED avoidance were higher for participants lacking confidence in health service response to non-COVID-19 conditions (adjusted OR: 6.39; 95% CI 3.19 to 12.82) and COVID-19 (1.81; 1.19 to 2.77) and lower for those perceiving a low risk of being infected at a health provider (0.16; 0.07 to 0.38).Conclusion In our sample, confidence in health services and risk perception of infection at a health provider were associated with the decision to avoid the ED. These results suggest that policymakers and care providers need to mitigate the negative consequences of delayed healthcare; be aware of the implications of distrust and fear from those in need of healthcare and provide equally distributed safe alternatives to ED care.